Diversity and distribution of lepidopteran stemborer species and their host plants in Botswana - Moeng, Eva; Mutamiswa, Reyard; Conlong, Des E.; Assefa, Yoseph; Le Ru, Bruno P.; Goftishu, Muluken; Nyamukondiwa, Casper (Springer, 2022)
Lepidopteran stemborers are amongst the most important insect pests of maize, sorghum and sugarcane in sub-Saharan Africa. With the exception of Chilo partellus (Swinhoe), which was accidentally introduced into Africa, the other stemborer pests are indigenous to the continent and have co-evolved with native grasses and sedges. In addition to pest species, wild habitats harbour diverse non-economic stemborer species, some of which are new to science. However, the diversity and distribution of both non-economic and pest species of stemborer are currently mostly unknown in Botswana. Accordingly, country-wide surveys were conducted during 2014/15 and 2015/16 austral summer to determine species diversity and distribution in cultivated and wild host plants of stemborers in Botswana. A total of 1597 stemborer larvae and 228 pupae were collected, constituting 63.1 and 36.9 larvae and 84.8 and 15.2% pupae from cultivated versus wild habitats, respectively. In addition to C. partellus, Sesamia calamistis Hampson and Eldana saccharina Walker which were previously reported, 12 more stemborer species were recorded for the first time in Botswana, including nine undescribed species. These species were from the Sciomesa, Sesamia and Conicofrontia genera and Tortricidae and Pyralidae families. Fourteen wild host and two cultivated host plant species of stemborers were recorded. Chilo partellus was most abundant (89.5%) in cultivated habitats whilst E. saccharina (33.6%) was most abundant in wild habitats. Stemborer species diversity was higher in wild habitats than cultivated. Current results highlight the significance of wild, especially wetland habitats for ecological functions and conservation of lepidopteran stemborer biodiversity.